After neonatal care, what next? A qualitative study of mothers’ post-discharge experiences after premature birth in Kenya - Justinah Maluni; Dorothy Oluoch; Sassy Molyneux; Mwanamvua Boga; Caroline Jones; Florence Murila; Mike English; Sue Ziebland; Lisa Hinton (International Journal for Equity in Health)
Abstract Background Approximately 15 million babies are born prematurely every year worldwide. Sub-Saharan Africa (SSA) and Asia account for more than half of the global preterm deliveries. Prominent healthcare structural and socio-economic factors in SSA, for example poverty and weak health systems, amplify vulnerabilities for mothers and premature babies; often leading to poor outcomes. Post-discharge mortality rates are high, and readmission is common. For mothers of premature babies, the transition home from hospital is marked by challenges and uncertainties. This study explored the post-discharge experiences of mothers of premature babies with the aim of identifying their needs and suggests strategies to strengthen and support their discharge preparation to care for their premature baby at home, and to and reduce mortality and readmission rates. Methods Narrative interviews were conducted face-to-face in English or Swahili with 34 mothers of premature babies recruited from two public hospitals and a social support group in Nairobi, Kenya between August—November 2021. Interviews were audio and video-recorded and transcribed for analysis. After transcription, the interviews were translated, where applicable, and thematic analysis was undertaken. Results For mothers of premature babies, discharge from neonatal care and the transition home is a complex process marked with mixed emotions; many reported feeling unprepared and facing stigma while in hospital and in their communities. Mothers described the emotional challenges of discharge from the neonatal unit and their information and support needs. Minimal involvement in their baby’s care while in the neonatal unit appeared to contribute to the mothers’ lack of confidence in caring for their babies independently post-discharge when they no longer had the support of the clinical and nursing staff. Insufficient information provided on discharge hindered a smooth transition to home, highlighting the need for information to support mothers’ confidence after discharge. Stigma relating to beliefs around preterm births was experienced by some of the mothers in the community and within some health clinics. Conclusions To support transitions home, strengthening the timing and adequacy of information provided to mothers at discharge from the neonatal unit in low-income settings in SSA and Asia – such as Kenya—is essential. Introducing strategies to build and assess mothers’ competencies with skills such as breastfeeding and identifying signs of deterioration before discharge could support their smooth transition home. Targeted engagement interventions at the community level could demystify and address stigma and knowledge gaps about premature deliveries at the community and social levels more broadly and within the health system.